Language variables atlas of Khoshnawaty accent - Hameed, Sakar A.; Saeed, Youssef Sh. (Humanities Journal of University of Zakho, 2019)
Dialect Atlas includes a group of language maps that contain the spread of a linguistic phenomenon in a certain area. In such atlases, phonetic, linguistics, and moral characteristics of language users of the original region inhabitants are specified. In geographical dialectology, areas and linguistic contexts are very important to the study. The researcher in the presented study tries to investigate and analyze the linguistic, phonological, and vocabulary differences in the chosen areas to map them in a linguistic atlas. The investigation involves 10 phonological variables in descriptive field research. The variables are written in IPA. The variables are added to the atlases in different symbols. The study is of two parts. The first part is the theoretical background that includes definitions of types of dialectology. The second part is the field research that includes the analysis and application of the study to 10 linguistics samples in the shape of words and symbols to be added to the specific maps that are prepared for this study. An Introduction chapter comes at the beginning of the study and a conclusion chapter comes at the end of the study followed by the abstract in both English and Arabic.